Anti-Microbial Activities of Shallots (Allium cepa L.) Extract and Garlic (Allium sativum L.) Extract on the Growth of Peat Soil Bacteria - Chaidir Adam (Bioscience, 2021)
This study aims to examine the antimicrobial activity of red onion (Allium cepa L.) and garlic (Allium sativum L.) extracts on the growth of peat soil bacteria. This type of research is an experimental study using a Completely Randomized Design with four levels of treatment. Test for bacterial activity using the agar diffusion method with the paper disc technique. Data were analyzed statistically using One Way Anova and the Games-Howell post-hoc test at the 5% significance level. The results showed that red onion (Allium cepa L.) and garlic (Allium sativum L.) extracts had antimicrobial activity against the growth of tested bacteria as indicated by the presence of a clear zone as an indicator of inhibition of bacterial growth. Garlic has better antimicrobial activity seen from the diameter of the clear zone that appears in the garlic extract treatment ranging from 8-13 mm, whereas in the treatment of onions it ranges from 3–5 mm.